Digital Project. - Smith, Lee Anne (Architectural Record, 2004)
This article presents information on Digital Project, which combines a powerful 3D software engine — with parametric tools for applying, tracking, and processing intelligent models of building systems — and the ability to manage data needed to enable digital manufacturing methods. The software gurus at Gehry Partners have taken their CATIA expertise and turned it into a high-end suite of software applications tailored to manage the entire life cycle of design and construction projects.